Impact of a cancer education seminar on knowledge and screening intent among Chinese Americans: Results from a randomized, controlled, community‐based trial. Issue Volume 124:Issue S7(2018) (26th March 2018) - Fung, Lei‐Chun; Nguyen, Kim H.; Stewart, Susan L.; Chen, Moon S.; Tong, Elisa K.
Abstract : BACKGROUND: Cancer is the leading cause of death for Asian Americans. The authors evaluated the status of cancer prevention for Chinese Americans in San Francisco, which has had years of cancer prevention efforts. METHODS: Through a community‐based clinic serving Chinese Americans, a randomized, controlled trial (n = 395) was conducted among participants who attended either a cancer prevention seminar or biospecimen education seminar. Changes in knowledge, attitudes, and screening completion/intent were measured across and between seminar groups. RESULTS: Participants were mostly women who had low acculturation and education levels. Over two‐thirds to almost all participants knew about modifiable risk factors for cancer and that screening tests were available, including for lung cancer. The majority of women had already completed mammography and Papanicolaou (Pap) tests. Approximately one‐half reported having completed colorectal cancer screening, prostate screening, or hepatitis B screening. Most were nonsmokers, but about one‐half "strongly agreed" that they would want a test for tobacco smoke exposure. After the cancer prevention seminar, significant increases within group were noted for knowledge (eating healthy foods, from 93.1% to 97.7% [ P  = .0002]; secondhand smoke causes cancer, from 66.3% to 74.8% [ P  = .04]) and for screening completion/intent (colorectal cancer, from 58.1% to 64.5% [ P  = .002] cervical cancer, from 72.9% to 75.5% [ P  = .04]) and there was a trend toward an increase for prostate cancer (from 50.0% to 61.1%; P  = .10). There was a significant change between groups for eating healthy foods ( P  = .004). CONCLUSIONS: The current reports documents the gains in cancer prevention among Cantonese‐speaking Chinese Americans, fostered by academic, community, and public health efforts. A community‐based seminar demonstrated improvement in some cancer knowledge or screening intent and opportunities for continued efforts. Cancer 2018;124:1622‐30. © 2018 American Cancer Society . Abstract : Because cancer is the leading cause of death for Asian Americans, the authors evaluate the status of cancer prevention for Chinese Americans in San Francisco, which has had years of cancer‐prevention efforts. This study documents the gains in cancer prevention among Cantonese‐speaking Chinese Americans, fostered by academic, community, and public health efforts, and the opportunities for continued cancer prevention efforts.